Embryological results in married couples with combination of male and female factors - O. M. Nosenko; A. I. Seylova (Kazimierz Wielki University, 2019)
The treatment of married couples with a combination of male and female infertility factors is quite complicated and often requires assisted reproductive technologies (ART), but according to ESHRE, after ICSI, the pregnancy rate is 28.4% for aspiration and 35.0% for transfer. One of the ways to improve the effectiveness of ART in this case is to use additional methods of selection of sperm and fertilized oocytes. The purpose of the study was to evaluate the embryological results of conducting cycles of ART in married couples with a combination of female and male infertility factors using modern methods of selection of sperm and embryos. Material and methods. There were 213 married couples of group I under prospective observation with a combination of male and female factors who had applied for ART. All men in group I suffered from pathozoospermia. Control group K consisted of 34 couples with secondary infertility of tube genesis, who consisted of conditionally somatically healthy women with a history of childbirth, without fallopian tubes, and their men with normozoospermia. The study group I was randomized into two groups: the main group A (n = 100) - the ART cycle was performed according to the proposed personalized method with additional methods for the selection of gametes and embryos; comparison group B (n = 113) - pre-conceptual training and the ART cycle were performed according to conventional methods. Groups A and B were stratified each into 3 subgroups. The A1 (n = 32) and B1 (n = 36) subgroups included married couples in whom women had chronic anovulation; in subgroup A2 (n = 37) and B2 (n = 35) - married couples in whom women had tubal infertility; in subgroup A3 (n = 31) and B3 (n = 42) are married couples in which women had a combination of tubal and anovulatory factors of infertility. Group A used additional methods for the selection of sperm and embryos: fluorescence in situ hybridization, examination of morphology of organelles of moving sperm at magnification × 6 600, time lapse microscopy of embryos and comparative genome-hybridization, sequencing of the new generation. Results. The use of modern methods for the selection of gametes and embryos has resulted in a statistically significant increase in the percentage of mature oocytes from the total number of oocytes by 1.18 times, the number of received embryos from one woman - by 1.27, the number of received embryos of excellent and good quality per woman - by 1.85, the percentage of embryos of excellent and good quality from the total number of embryos - 1.45 times. Conclusions. In patients with a combination of male and female infertility factors, additional selection of gametes and embryos is a way to improve the effectiveness of infertility treatments in the ART cycles.